The indication of double-sensors in living plant cells on the invisible damage of soybean plants under low-dose La(III) exposure - Xin Wang; Yue Ben; Wanxin Liu; Qing Zhou; Lihong Wang; Xiaohua Huang (Ecological Indicators)
Rare earth elements (REEs) are a type of frequently reported emerging pollutant that affects plant growth. The harm caused by continuous exposure to low-dose REEs has rarely been studied. Quickly, accurately, and non-invasively monitoring the continuous influence of low-dose REEs on plant growth in situ is key to indicating and warning of its harm to plants and ecosystems. In this study, after continuous exposure to low-dose lanthanum [La(III), a REE] for 14 days, invisible damage occurred in leaf cells, and La accumulated continuously in the soybean plants (leaves > stems > roots > pods > seeds), causing potential human health risks. Two proteins [vitronectin-like protein (VN) and arabinogalactan proteins (AGP)] in leaf cells that bound La(III) were selected as biomarkers, and changes in these two proteins were detected by constructing dual-sensors in living leaf cells after continuous exposure to low-dose La(III) for 14 days. The results showed that the electrochemical outputs from leaf cells–the electron transfer resistance Ret(VN) and Ret(AGP)–were related to the damage indices such as MDA, chlorophyll content, electrolyte leakage, cell vitality, fresh and dry weight of leaves, and leaf area. Using this output, two warning intervals of visible damage were obtained: Ret(VN) was 8.53 %–47.22 %, and Ret(AGP) was 12.75 %–51.31 %. This study successfully demonstrated the real-time in situ detection of plant cell biomarker changes and invisible damage under low-dose La(III) exposure, providing methods for early warning monitoring of plant damage caused by low-dose continuous exposure to REEs.